THE EVOLUTION OF FRENCH LANGUAGE TEACHING IN THE MOROCCAN CONTEXT: BETWEEN LANGUAGE POLICY AND SCHOOL POLICIES - Khadija LEMSSIAH; Malika BAHMAD (Universitaria Publishing House, Craiova, 2024)
Since gaining independence, Morocco's educational system has undergone a continuous process of modernization, reflecting both the inherent need for constant renewal and the evolving aspirations of a society embracing a globalized future. This dynamic has significantly impacted French language teaching (FLE). This works aims to explore the evolution of FLE instruction in Morocco by examining key reforms implemented over time; reforms which were marked by substantial changes, culminated in the publication of several official reference texts: the 1994 Pedagogical Recommendations, the 2002 Pedagogical Guidelines, and the 2007 Pedagogical Guidelines. Through a brief historical overview, this work sheds light on how FLE instruction has adapted to the Moroccan context, driven by evolving language and educational policies.